MASALAH-MASALAH YANG DIALAMI SISWA SMP NEGERI 3 RUMBIO JAYA - Yakub, Elni; Arlizon, Raja; ', Sunarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this research are 1) how are the descriptions of personal problem experienced by male and female students?, 2) how are the descriptions of emotional problem experienced by male and female students, 3) how are the descriptions of learning problem experienced by male and female student?, 4) how are the descriptions of family problem experienced by male and female student?, 5) how are the descriptions of social problem experienced by male and female student?, 6) how are the general description of the problems that experienced by male and female students, 7) how about the category of problems that experienced by the male and female students in general. The data instrument is a questioner regarding to problems that experienced by the students. The population of this research is all ofthe students in class VIII and IX in Senior High School Number 3, Rumbio Jaya, academic year 2015/2016. The sample is determined by using total sampling technique that means all of the population is the sample. The result of this study shows that the description of personal problem experienced by male and female students mostly included in â€œmiddle â€œ category, male 78% and female 82%, 2) the description of emotional problem experienced by the male and female students is mostly in â€œmiddleâ€ category, male 51% and female 54%, 3) the description of learning problem experienced by the male and female students is mostly in â€œmiddleâ€ category, male 55% and female 54%, 4) the description of family problem experienced by the male and female students is mostly in â€œfewâ€ category, male 88% and female 92%, 5) the description of social problem experienced by the male and female students is mostly in â€œfewâ€ category, male 82% and female 91%, 6) In general, the description of the problems experienced by male and female students are mostly about personal, emotional and learning, 7) the description of problems experienced by the male and female students based on the aspect of personal, emotional, learning, family and social in general is in â€œmiddleâ€ category.Keyword : The Problem Of Student